How Speech Contests Should Engage with AI: Focusing on Discussions from the Central Asia Speech Contest - Noto, Kuniyuki; O‘rinboeva, Xayotxon (The Lingua Spectrum, 2025)
In recent years, the emergence of generative artificial intelligence has fundamentally transformed language education. The meaning and value of speech contests in Japanese language education have been especially affected. Originally, these contests allowed learners to demonstrate their Japanese competence, but with the spread of AI-generated and AI-edited texts, assessing genuine linguistic ability has become increasingly difficult. Completely prohibiting AI use is also unrealistic, as compliance cannot be effectively monitored. Thus, the issue is shifting from “how to restrict AI” to “how to redefine the purpose of speech contests in an AI-integrated era.” This paper argues for reexamining the core goals of speech contests under the influence of AI. If they remain mere ceremonial events, their educational significance will inevitably fade. The challenge for today’s language education is to design new types of contests that coexist with AI and reflect a renewed concept of language competence. In this respect, Japanese language education in Uzbekistan holds unique potential to pioneer innovative contest models grounded in this emerging perspective.